Investigation on the effect of acetylation and the resin type on the biological resistance of aspen tree layered particleboard - Kazem Dost Hosseini (Regional Information Center for Science and Technology (RICeST), 2011)
This research was conducted to evaluate the effects of acetylation and the resin type on three layered populus particleboard against white-rot fungus, Trametes versicolor. Populus particles were acetylated at three levels of acetyl content (WPG of 0, 8.39% and 17.27%). In manufacturing of single and three layered boards with acetylated particles two type of resin, urea formaldehyde and isocyanate( as adhesives) were employed.